Sekolah Inspirasi Bersama BEM KM UNP di SDN 17 Gunung Pangilun Kota Padang - Abdul maulub hrp; Yana Yana Lendarwati (Universitas Negeri Padang, 2022)
A student besides having an obligation to go to college, complete assignments, but also has to care about the community environment outside the campus. Loyal activists highly uphold social values ​​who have a sense of self-awareness of the role of activists as agents of change in terms of being able to become the figure expected of them. can bring changes for the better from various aspects besides that Students need to develop critical thinking so they can see things in more depth and find other sides that are not found by many others. In social conditions that seem fine, students can see that something is not okay, such as things in the world of education. Therefore this community service activity is an activity that goes directly into the field with the aim of realizing social sensitivity as a part of from elements of the community in the form of one day dedication at elementary schools in the form of visiting, interacting, teaching and providing motivation and inspiration.